Analysis of the Seepage Due to the Thawing of Permafrost, Considering the Gradient of the Impermeable Layer. (2017) - Ogawa, Masaya; Kanie, Shunji
Abstract: Topographical deformation due to global warming has become a serious problem. However, scientific studies have not been sufficiently conducted to understand the mechanisms. Solifluction, a gradual mass movement related to freeze-thaw processes, is known as a typical topographical deformation. The purpose of this study is to simulate the solifluction process considering the seepage influence, and then establish a predictive numerical model. The authors adopted the Finite Volume Method (FVM) and Dupuit's assumption in order to precisely simulate the seepage flow. Consequently, according to this study, the authors suggested to adopt a non-linear assumption for appropriate estimation of seepage flow velocity.